Measurement of shear strength and interface parameters by multi-stage large-scale direct/interface shear and pull-out tests. (28th June 2018) - Xu, Youwei; Williams, David J; Serati, Mehdi
Abstract: It is essential to measure the shear strength of soils and interface parameters between soils and geosynthetics for the safe design and stability analysis of geosynthetic-reinforced soil structures. These parameters recommended for engineering projects are normally measured by laboratory single-stage direct/interface shear and pull-out tests. The conventional single-stage tests are carried out on at least three representative specimens under three different normal stresses. However, a large quantity of specimens is required for large-scale tests, with tedious sample preparation procedures, so that large-scale single-stage testing becomes very labour intensive, time consuming and expensive. Given that the multi-stage testing method is able to measure the shear strength parameters by testing only one representative specimen, this paper investigates the feasibility, reliability and applicability of the multi-stage testing method in large-scale direct/interface shear and pull-out tests. Two compacted soils and a geogrid were tested using both single-stage and multi-stage tests. It was found that the shear strengths obtained from the multi-stage tests were slightly lower that those obtained from the single-stage tests, and the inferred apparent cohesion and friction angle matched closely. In addition, the limitations of the multi-stage testing method were highlighted. The measured direct shear strength of the soils, the interface shear strength and pull-out shear strength between the soils and the geogrid are also compared and discussed in this paper.